Photoemission cross section：A critical parameter in the impurity photovoltaic effect - 袁吉仁 黄海宾 邓新华 岳之浩 何玉平 周耐根 周浪 (Chinese physics B, 2017)
A numerical study has been conducted to explore the role of photoemission cross sections in the impurity photovoltaic（IPV） effect for silicon solar cells doped with indium. The photovoltaic parameters（short-circuit current density, opencircuit voltage, and conversion efficiency） of the IPV solar cell were calculated as functions of variable electron and hole photoemission cross sections. The presented results show that the electron and hole photoemission cross sections play critical roles in the IPV effect. When the electron photoemission cross section is 10^-20cm^2, the conversion efficiencyη of the IPV cell always has a negative gain（△η 0） if the IPV impurity is introduced. A large hole photoemission cross section can adversely impact IPV solar cell performance. The combination of a small hole photoemission cross section and a large electron photoemission cross section can achieve higher conversion efficiency for the IPV solar cell since a large electron photoemission cross section can enhance the necessary electron transition from the impurity level to the conduction band and a small hole photoemission cross section can reduce the needless sub-bandgap absorption. It is concluded that those impurities with small（large） hole photoemission cross section and large（small） electron photoemission cross section,whose energy levels are near the valence（or conduction） band edge, may be suitable for use in IPV solar cells. These results may help in judging whether or not an impurity is appropriate for use in IPV solar cells according to its electron and hole photoemission cross sections.